What Influences Bank Lending in Saudi Arabia? - Miyajima, Ken (IMF Working Papers; Working Paper ;, 2017)
Determinants of bank-level credit growth in Saudi Arabia are investigated by applying a panel approach to data spanning 2000-15. Strong bank balance sheet conditions, economic activity, and oil prices support bank lending. Reduced bank concentration appears to have helped. Lending remained robust in 2015 despite oil prices having declined, helped by strong bank balance sheets and a reduction in bank holdings of 'excess liquidity'. To support bank lending in the period ahead, bank balance sheets need to remain strong. Fiscal adjustment and a reduced reliance on banks to finance the budget deficit would support credit provision to the private sector.